2008
DOI: 10.1021/la803223r
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Forces and Contact Angles of Water Strider Legs

Abstract: This study investigated the adhesion (pull-off) force and contact angles of a water strider's leg. During hydrostatic experiments, the adhesion force was found to be 2 dyn. The image of a cross section of a live leg contacted with a deformed water surface provided the contact angle of 168.8 degrees . A numerical scheme was proposed to determine the water surface on a groove wall of a seta. The results showed that the asperities of a seta are almost wetted, and the fraction of the wetted projection area was 0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 29 publications
(46 reference statements)
2
21
0
Order By: Relevance
“…DP s ; S is the area of the contact region between the water droplet and the surface; G is the gravitational force acting on the lower part of the water droplet, and F c is the surface tension from Eq. (2).…”
Section: Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…DP s ; S is the area of the contact region between the water droplet and the surface; G is the gravitational force acting on the lower part of the water droplet, and F c is the surface tension from Eq. (2).…”
Section: Characterizationsmentioning
confidence: 99%
“…Therefore, exploring the relationship between surface wettability and micro-/nanostructures of biological species is the first step to prepare smart bio-inspired surface materials [1][2][3][4][5][6][7][8][9]. In nature, some plant surfaces, including their fruits, play an important role in protecting plants from water loss, UV and visible radiation, temperature extremes, and so forth [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, little has been focused on another special contact state of a droplet on hydrophobic surface called "Gecko state" (high adhesive superhydrophobicity). The superhydrophobic material with high adhesion can be used as a "mechanical hand" in no-loss microfluidic transport [3]. After millions of years of evolution, many animals and plants have possessed distinctive body surfaces which are superhydrophobic, self-cleaning, anti-adhesive, anti-corrosive and anti-wearing [4].…”
Section: Introductionmentioning
confidence: 99%
“…The front legs are equipped with a hunting hook approximately the same size as the leg diameter. The front legs are also used to dewet the middle and back legs [21]. The entire insect is coated in an organic wax, which is typically assumed in literature to have contact angle ~105° with water [1,18,22].…”
Section: Water Stridersmentioning
confidence: 99%
“…In the case of water striders, it has been shown that both orders of roughness in the hierarchical structure must be present in order for the strider leg to be physically capable of achieving the measured 170° contact angle [1]. The following equation incorporates setae features into the Cassie-Baxter wettability equation [1,21]:…”
Section: Wettingmentioning
confidence: 99%